Kepuasan Peserta JKN terhadap Kualitas Pelayanan Kesehatan Menggunakan Indikator HCAHPS di Instalasi Rawat Inap RS Stella Maris Makassar Indonesia Tahun 2015 - A. Indahwaty Sidin; Noer Bahry Noor; Nur Adayanti (Jurnal Kebijakan Kesehatan Indonesia, 2016)
Currently, a lot of information dispersed in community in terms of unsatisfaction of social health insurance members regarding health services even though in SHI road map 2012-2019, the target of satisfaction is e” 75%. Stella Maris hospital, as one of older privates hospital having good reputation in Makassar, have provided health services for SHI’s members since 2014. For that reason, this study is conducted to find the description of SHI member’s satisfaction toward quality of health services applied indicators of Survey Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS). The population number was 482, the sampling method is proportional stratified random sampling and the sample was 120 respondents. The results showed that there are 97,5% of respondents satisfied with doctor communication, 2,5% of respondents were unsatisfied. As for nurse communication dimension, 94,2% of respondents perceived satisfaction and it is only 5,8% of patients are unsatisfied. The result also showed that 96,7% of respondents are satisfied with nurse’s responsiveness and it was only 1,7% of respondents unsatisfied. Furthermore, as for doctors’ responsiveness, satisfied respondents are 98,3% and unsatisfied respondents were 1,7%. As for Communication regarding of pharmacy services, satisfied respondents are 94.2% respectively, while unsatisfied respondents are 5,8% respectively. Moreover, there are 90% of satisfied respondents and 10% of unsatisfied respondents. The other dimensions are food services in hospital. There 91,7% of satisfied respondents. In conclusion, there are an average of 99,2% of satisfied respondents in toward quality health services consisting of 7 dimensions, they are in doctor’s communication, nurse’s communication, doctor’s responsiveness, nurse responsiveness, communication regarding pharmacy services, environment and food services. Latar Belakang: Saat ini banyak informasi di media tentang ketidak puasan peserta JKN. Sedangkan dalam roadmap JKN 2012 telah ditargetkan minimal kepuasan pasien peserta JKN e” 75%. RS Stella maris adalah salah satu RS swasta tertua di Makassar yang memiliki reputasi cukup baik, pada Tahun 2014 juga telah melayani peserta JKN. sehingga penelitian ini bertujuan untuk memperoleh gambaran kepuasan pasien peserta JKN tentang kualitas pelayananan kesehatan di Instalasi Rawat Inap RS Stella Maris Makassar Tahun 2015. Metode: Jumlah populasi dalam penelitian ini sebanyak 482 responden dan penarikan sampel menggunakan proportional stratified random sampling dengan jumlah sampel 120 responden.Penelitian ini menggunakan indikator kualitas pelayanan Survey Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS). Hasil: Penelitian ini menunjukkan bahwa tingkat kepuasan pasien terhadap kualitas pelayanan berdasarkan dimensi komunikasi dokter, puas (97,5%) dan tidak puas (2,5%). Dimensi komunikasi perawat, puas (94,2%) dan tidak puas (5,8%). Dimensi daya tanggap dokter, puas (98,3%) dan tidak puas (1,7%). Dimensi daya tanggap perawat, puas (96,7%) dan tidak puas (3,3%). Dimensi komunikasi obat, puas (94.2%) dan tidak puas (5,8%). Dimensi lingkungan, puas (90%) dan tidak puas (10%). Dimensi pelayanan makanan, puas (91,7%) dan tidak puas (8,3%). Tingkat kepuasan pasien tentang kualitas pelayanan di Instalasi Rawat Inap RS Stella Maris Makassar, puas (99,2%) dan tidak puas (0,8%). Kesimpulan: Pasien peserta JKN puas terhadap komunikasi dokter, komunikasi perawat, daya tanggap dokter, daya tanggap perawat, komunikasi obat, lingkungan, dan pelayanan makanan.